Broadband PWM Power amplifier using approximate 2DOF digital controller - Hiroshi Iwata (2018)
Lately, it is required that the bandwidth of PWM power amplifier is extended. For example, it is in application of the testing power supply of a low ferquency immunity examination, or a class-D ampllifier. In this paper, we show that the bandwidth of PWM power amplifier can be extended by using an Approximate 2DOF Digital Controller. This controller is implemented on a DSP. It is demonstrated from experiments that the bandwidth can be made wider with this controller.